Bronchiectasis Exacerbations: Definitions, Causes, and Acute Management - Perl, Sivan; Shteinberg, Michal (Seminars in Respiratory and Critical Care Medicine, 2021)
Pulmonary exacerbations (PExs) are events in the course of bronchiectasis which are defined as an increase in disease symptoms lasting a period of a few days. It is established that the tendency toward having PEx is stable throughout the course of the disease. Certain conditions were found to be associated with an increased risk of developing a PEx. Among these are chronic airway infection with Pseudomonas aeruginosa or Aspergillus species, concomitant airway diseases (asthma, chronic obstructive pulmonary disease, and chronic rhinosinusitis), genetic factors such as primary ciliary dyskinesia, and nutritional factors. The immediate events underlying the onset of a PEx are less clearly determined. Although acute changes in bacterial airway composition have been the paradigm for decades, recent microbiome-focused research has not uniformly established such acute changes at the onset of PEx. Other acute changes such as air pollution, viral infection, and changes in bacterial metabolic activity have also been implicated as causes of a PEx. Despite these gaps in our knowledge of the biology of PEx, antimicrobial therapy directed against the identified pathogens in sputum is currently the recommended therapeutic strategy. Various long-term therapies, including antimicrobial and anti-inflammatory strategies, have been proven effective in reducing the frequency of PEx, leading to a recommendation for the use of these strategies in people with frequent PEx.
Keywords: bronchiectasis; pulmonary exacerbation; inflammation; respiratory infections